Visible Light Communications - Wang, Jin-Yuan (IntechOpen, 2017)
Visible light communication (VLC) has drawn much attention recently. Compared to the traditional radio frequency wireless communications (RFWC), VLC has many advantages, such as worldwide availability, high security, large bandwidth, immunity to radio frequency interference, and unlicensed spectrum. Due to its superiority, VLC has become a complementary solution to the overcrowded RFWC. This book intends to introduce the latest research progress in VLC, which covers the novel modulation techniques for VLC, the multiple input multiple output (MIMO) techniques for VLC, the collaborative communication techniques for VLC, and the practical applications of VLC. The book is a useful resource for researchers, engineers, scientists, and students interested in understanding and designing VLC systems.